2015
DOI: 10.1186/s13054-015-0827-7
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop assisted versus manual goal-directed fluid therapy during high-risk abdominal surgery: a case–control study with propensity matching

Abstract: IntroductionGoal-directed fluid therapy strategies have been shown to benefit moderate- to high-risk surgery patients. Despite this, these strategies are often not implemented. The aim of this study was to assess a closed-loop fluid administration system in a surgical cohort and compare the results with those for matched patients who received manual management. Our hypothesis was that the patients receiving closed-loop assistance would spend more time in a preload-independent state, defined as percentage of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 29 publications
0
52
0
1
Order By: Relevance
“…The same group extended their system with a minimal invasive cardiac output system measuring stroke volume variation (EV1000, Edwards Lifescience, Irvine, California, USA) and compared its performance to maintain a preload independent state with a manual goal-directed fluid therapy. Also in this case-control study, the closedloop treated group showed a significantly greater portion of case time in a preload independent state compared with the manually treated group [62].…”
Section: Closed-loop Controlmentioning
confidence: 56%
“…The same group extended their system with a minimal invasive cardiac output system measuring stroke volume variation (EV1000, Edwards Lifescience, Irvine, California, USA) and compared its performance to maintain a preload independent state with a manual goal-directed fluid therapy. Also in this case-control study, the closedloop treated group showed a significantly greater portion of case time in a preload independent state compared with the manually treated group [62].…”
Section: Closed-loop Controlmentioning
confidence: 56%
“…We assumed group size imbalance may exist between AM and PM case starts due to the consistent morning starts in all ORs. We knew if we could pull at least 300 patients into the former and 100 patients into the latter, assuming the typical patient received 2100 ± 450 ml of fluid based on previous work 12 , with a power of 0.8 and alpha of 0.05, we would sufficiently power our analysis to detect a difference of approximately 300ml of fluid between the groups. With a minimum NPO time difference of 2.5 hours between groups, this represented the ability to detect a need of as little as 120 ml of 'deficit' fluids between groups per hour of NPO time.…”
Section: Statistical Analysis and Outcomesmentioning
confidence: 99%
“…An ultimate system such as this should not only automatically administer fluid therapy, because it has already been successful for major noncardiac surgery, 28 but should also automatically deliver vasoconstrictors and inotropic agents when low systemic vascular resistance and low cardiac output syndrome are present. A combined optimal robotic anesthesia and perfusion system for cardiac anesthesia that would reduce attending anesthesiologists' workload, allowing them to concentrate on a higher level of care requiring human intelligence, will make a difference in cardiac patients' outcomes.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%